Tube Pancreatico-Duodenostomy for Management of a Severe Penetrating Pancreaticoduodenal Injury - Hatzigeorgiadis, Anestis; Boulas, Konstantinos A; Barettas, Nikolaos; Papageorgiou, Irene; Blouhos, Konstantinos (JOP. Journal of the Pancreas, 2014)
Context Optimal management of penetrating pancreaticoduodenal injuries and better outcomes are associated with simple, fast damage control surgery and shorter operative time. The performance of pyloric exclusion and tube duodenostomy has markedly decreased. However, there is still a trend toward their performance in cases of delay duodenal repair or severe pancreaticoduodenal injury. Case report The present report describes a case of a hemodynamically stable patient with a single penetrating gunshot trauma causing an AAST-OIS grade III pancreatic head injury and grade IV injury of the second portion of the duodenum. The patient was treated in our Level IV rural trauma center and submitted to primary closure of the posterolateral duodenal wall (the laceration of the contralateral inner medial duodenal wall could not be repaired), external duodenal and pancreatic drainage, and duodenal decompression by tube pancreatico-duodenostomy (insertion of a 18 Fr Foley catheter through the laceration of the pancreatic head toward the duodenal lumen), tube cholangiostomy, and pyloric exclusion accompanied with a feeding jejunostomy. Conclusions Tube pancreatico-duodenostomy, which is described for the first time in the literature, turned out to be effective and can be considered as an option in pancreaticoduodenal trauma when the inner medial duodenal wall cannot be repaired. Image: Gunshot.